Assessment of the indoor environmental conditions of a baroque library in Portugal - Pereira, Luísa Dias (2017)
This paper presents the preliminary results of the study of the indoor environmental conditions in a Baroque building of a XVIII century library, located in the heights of the historic centre of the University of Coimbra (UC), which was established 727 years ago. Since these conditions play a very important role in the conservation of the books and the wood bookshelves, experimental surveys based on permanent measurements of the hygrothermal air conditions and of particulate matter concentrations are being carried out since early October 2016. Some early results of this short term study are presented and discussed.